THE EFFECT OF INQUIRY MODEL IN IPAS LEARNING ON STUDENTS’ CRITICAL THINKING ABILITY - Nisfullailatul Fitriya; Vanda Rezania (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
The low level of critical thinking skills in elementary schools has a significant impact on the development of the times. This skill is essential in today's digital and modernized era. A learning model is needed to improve critical thinking skills, especially in social studies learning. Researchers focus more on social studies learning related to how students identify problems in the community. This study aims to determine the effect of the inquiry model on students' critical thinking skills. This study uses a quantitative research method with a one-group pretest-posttest design. The sample used in this study amounted to 14 Utsman IV class students because they used saturated sampling techniques and student responses according to relevant criteria. Data collection for this study utilized pretest and posttest data. Data analysis was conducted using SPSS version 26. The data analysis technique used to test the hypothesis in this study employed a paired sample t-test, which yielded a value of 0.000 < 0.05, indicating an increase in students' critical thinking skills. Thus, the results of this study reveal the influence of the inquiry model on social studies learning on students' critical thinking skills. Keywords: Critical Thinking, Inquiry Model, IPAS Learning